What is the middle term of the product of (x + 5)(x + 2)?
7x
10x
18x

Question

Asked 11/19/2014 10:32:08 AM

Updated 11/19/2014 8:07:04 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/19/2014 8:07:04 PM]

monnize|Points 0|

vchutkan|Points 6464|

pritilixious|Points 238|

asero1010|Points 4484|

Shanaaz1986|Points 480|

Shanaaz1986|Points 480|

Shanaaz1986|Points 480|

jeifunk|Points 37156|

migzptz|Points 7632|

Question

Asked 11/19/2014 10:32:08 AM

Updated 11/19/2014 8:07:04 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/19/2014 8:07:04 PM]

Rating

5

mr + ns - nr - ms

= m(r - s) + n(s - r)

= (r - s)(m - n)

= m(r - s) + n(s - r)

= (r - s)(m - n)

Added 11/19/2014 8:02:34 PM

5

n^3 - n^2 + 3n - 3

= n^2(n - 1) + 2(n - 1)

= (n - 1)(n^2 + 2)

= n^2(n - 1) + 2(n - 1)

= (n - 1)(n^2 + 2)

Added 11/19/2014 8:03:27 PM

5

a^2 - a - 20

= a*a - 5a + 4a - 5*4

= (a - 5)(a + 4)

= a*a - 5a + 4a - 5*4

= (a - 5)(a + 4)

Added 11/19/2014 8:07:02 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/20/2014 9:02:22 AM]

Find the greatest common factor of 15x 2 y 3 and -20x 3 yz.

Question

Not Answered

Updated 11/17/2014 9:09:13 PM

1 Answer/Comment

The greatest common factor of 15x^2y^3 and -20x^3yz is 5x^2y.

15x^2y^3 = 3*5x^2y^3

-20x^3yz = -4*5x^3yz

15x^2y^3 = 3*5x^2y^3

-20x^3yz = -4*5x^3yz

Added 11/17/2014 9:09:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 12:52:12 AM]

Divide 8y 7 ÷ 4y 5 **Weegy:** The result of (4y)^3/8y is 8y^2
**User:** find the right quotient.
36m 5 n 5 ÷ (12m 3) **Weegy:** 36m^5 n^5 ? (12m^3) = 3m^2 n^5 **User:** Find the quotient.
12 a3 p4 ÷ -2a2p
-6a3p5
-24ap3
-6ap3
6a5p3 **User:** Find the quotient.
4z a + 2 ÷ (-8z a - 2)
-z-4
-z
-z2a
-z4 (More)

Question

Not Answered

Updated 11/24/2014 12:29:05 AM

1 Answer/Comment

8y^7 ÷ 4y^5

= (8/4)*(y^7/y^5)

= 2*y^2

= 2y^2

= (8/4)*(y^7/y^5)

= 2*y^2

= 2y^2

Added 11/24/2014 12:28:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 12:54:47 AM]

Factor this expression completely : mr+ ns - nr - ms

Question

Updated 11/18/2014 10:13:57 PM

1 Answer/Comment

mr + ns - nr - ms

= mr - ms + n(s - r)

= m(r - s) + n(s - r)

= (r - s)( m - n)

= mr - ms + n(s - r)

= m(r - s) + n(s - r)

= (r - s)( m - n)

Added 11/18/2014 10:07:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 10:31:49 PM]

Find the quotient.
(4ab - 8a 2 + 12ac) ÷ 4a
b - 2a2 + 3c
b - 2a + 3c
abc **Weegy:** (4ab - 8a 2 + 12ac) ? 4a b - 2a2+ 3c b - 2a + 3c abc. If i find the quotient of this equation.
The answer is 5a+10b=25c **User:** Find the quotient.
48j 5 k 2÷ (-3j 3 k)
-16j2k
-16j3k2
-16j3k (More)

Question

Not Answered

Updated 11/15/2014 2:42:39 AM

2 Answers/Comments

(4ab - 8a^2 + 12ac) ÷ 4a

= 4ab/4a - 8a^2/4a + 12ac/4a

= b - 2a +3c

= 4ab/4a - 8a^2/4a + 12ac/4a

= b - 2a +3c

Added 11/15/2014 2:41:37 AM

This answer has been confirmed as correct and helpful.

48j^5k^2 ÷ (-3j^3k)

= -16j^2k

= -16j^2k

Added 11/15/2014 2:42:32 AM

This answer has been confirmed as correct and helpful.

Factor 2x 2 - 10x + 8 completely.
2(x + 2)(x - 2)
2(x - 1)(x - 4)
2(x - 2)(x + 4) User: Factor 4b 2 - 9.
(4b + 3)(b - 3)
(2b + 3)(2b - 3)
(2b - 4)(2b - 5) User: How many terms are in the polynomial abcd + e - h 2?
two
three
five
six

Question

Not Answered

Updated 11/16/2014 9:48:53 PM

1 Answer/Comment

34,462,968

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 792 [Total 6665] Ratings 18 Comments 612 Invitations 0 Offline

There are no comments.